RANCANGAN LEARNING MANAGEMENT SYSTEM TEKNIK NAVIGASI UDARA - Silvia Anggraini; Bambang Bagus Harianto; Dewi Ratna Sari (Journal of Public Transportation Community, 2023)
With its vast potential, information technology has revolutionized education through various innovations. The quality of the teaching and learning process has significantly improved with the aid of information technology. Face-to-face learning is no longer the sole option as the presence of an LMS eases the process of teaching and learning. In the course of developing an Air Navigation Engineering Learning Management System using the ADDIE method (Analysis, Design, Development, Implementation, and Evaluation), the design was implemented on WordPress due to its flexibility in integrating plugins. This LMS website for Air Navigation Engineering prioritizes material, material delivery, quizzes, assessments, and certificates. The website's data validation yielded an overall feasibility rate of 96.6%, as confirmed by objective validators. Multiple respondents attested to an overall usability rate of 96.2%. Efficient material delivery is facilitated through the use of instructional videos. Additionally, the website offers a payment system for accessing necessary materials.